Improving outcomes for amputees: The health-related quality of life and cost utility analysis of osseointegration prosthetics in transfemoral amputees. Issue 12 (December 2022) - Handford, C.; McMenemy, L.; Kendrew, J.; Mistlin, A.; Akhtar, M.A.; Parry, M.; Hindle, P.
Highlights: Osseointegration prosthesis following transfemoral amputation is both cost effective and quality of life enhancing in appropriately selected patients. Those who have performed poorly with traditional prosthetics, reflected by a EQ5D-HUV <0.60, should be offered osseointegration. A strong argument exists for osseointegration to be commissioned within publicly funded healthcare systems as a second line prosthetic treatment in transfemoral amputees. Abstract: Aim: Some amputees are unable to adequately ambulate using conventional socket prosthetics, osseointegrated prosthetics have been described as an alternative strategy in this patient group. This paper aims to assess the effect of osseointegrated prosthetics, commonly simply referred to as osseointegration, in transfemoral amputees on health-related quality of life and cost analysis. Methods: Two centre analysis of patients receiving transcutaneous femoral osseointegration using The Osseointegration Group of Australia Osseointegration Prosthetic Limb (OGAP-OPL) implant. Retrospective health utility and cost analysis of prospectively collected patient reported health outcome data. Osseointegration cost was compared with the yearly cost of a poorly fitting conventional prosthetic determining cost/Quality Adjusted Life Year. Results: Eighty amputees received osseointegration. Mean age was 39 years (range 20–57) and 66% were male ( n = 53). The majority of subjects underwent unilateral ( n = 62, 77.5%) rather than bilateral surgery ( n = 18, 22.5%). Trauma was the most common indication ( n = 59, 74%). Maximum follow up was 10.5-years. Mean preoperative EQ5D HUV in pooled data was 0.64 (SEM 0.025) increasing to 0.73 (0.036) at 5-years and 0.78 (0.051) at 6 years with continued improvement up to 10.5-years. In subgroup analysis those with a starting EQ5D HUV <0.60 reached a cost/QALY of <£30, 000 at 5-years postoperatively and show statistically significant improvement in EQ5D HUV. The UK military experience was wholly positive with a mean starting EQ5D HUV of 0.48 (0.017) with significant ( p < 0.05) improvement in EQ5D HUV at each time point and a resultant reducing cost/QALY at each time point being £28, 616.89 at 5 years. Conclusion: There is both a quality of life and financial argument in favour of osseointegration in select patients with above transfemoral amputations. In those unable to mobilise satisfactorily with traditional prostheses and a pre-intervention score of <0.60, a consistent cost effectiveness and quality of life benefit can be seen. Such patients should be considered for osseointegration as these patients reap the maximum benefit and cost effectiveness of the device. This evidence lends strongly to the debate advocating the use of osseointegration through centrally funded resources, including the NHS.